Meningkatkan Hasil Belajar Matematika Melalui Teknik Menyimpan Dengan Media Kantong Nilai Pada Siswa Kelas II SD Negeri Klepu - Arifati Munfaridah; Moh Masduki (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
This research aims to improve student learning outcomes in mathematics subjects including addition and multiplication in class II of SD Negeri 2 Klepu, Sooko District, Ponorogo Regency. This research is Classroom Action Research (PTK) which was carried out in 2 cycles. Each cycle consists of planning, action, observation, and reflection. The research subjects were 7 class II students at SD Negeri 2 Klepu, Sooko District, for the 2021/2022 academic year. Research data was obtained through observation and tests. Data analysis uses qualitative descriptive analysis techniques. The results of the research show that there are learning outcomes for class II students at SD Negeri 2 Klepu, Sooko District, through the application of saving techniques using value bag media. The increase in student learning outcomes is shown by an increase in average achievement of 28.6% in the pre-cycle, increasing again by 71.4% in cycle I, and increasing again to 100% in cycle II. Based on these results, it can be concluded that there has been an increase in the mathematics subject matter of addition and multiplication through the application of saving techniques using value bag media in class II of SD Negeri 2 Klepu, Sooko District, for the 2021/2022 academic year.